Whiskers as a novel tissue for tracking reproductive and stress-related hormones in North Pacific otariid pinnipeds. Issue 1 (12th January 2021) - Keogh, Mandy J; Charapata, Patrick; Fadely, Brian S; Zeppelin, Tonya; Rea, Lorrie; Waite, Jason N; Burkanov, Vladimir; Marshall, Chris; Jones, Aubree; Sprowls, Caitlin; Wooller, Matthew J
Abstract : We measured reproductive and stress-related hormones in whiskers from female northern fur seals and Steller sea lions. Progesterone concentrations displayed cyclical patterns. Stable isotope signatures provided a tool to differentiate years within whiskers and when paired with progesterone concentrations may aid in identifying active gestation or skipped reproductive years. Abstract: Keratinized tissues, including whiskers, are ideal for acquiring a record of physiological parameters. Most tissues provide a snapshot of physiological status; however, whiskers may support longitudinal sampling for reproductive and stress-related hormones, if hormones are incorporated as whiskers grow and concentrations change with physiological state. Whiskers from female Steller sea lions ( Eumetopias jubatus ) and northern fur seals ( Callorhinus ursinus ) were serially sectioned and pulverized and steroid hormones were extracted. Standard methods were used to validate enzyme immunoassay kits for cortisol, progesterone, 17β-estradiol and testosterone. All hormones were measurable in whisker segments from both species with progesterone concentrations showing cyclical patterns, which appear to signify previous pregnancies or luteal phases. Yearly progesterone concentrations were greater in years a pup was produced compared with years when no pup was observed. Free-ranging female Steller sea lions had reproductive rates between 0 and 1.0 (0.53 ± 0.33, n  = 12) using a yearly progesterone concentration of 30 pg/mg or greater to classify a reproductive year as producing a pup and below 30 pg/mg as non-reproductive. Cortisol concentrations were greater near the root and rapidly declined, lacking any obvious patterns, throughout the rest of the whisker. Progesterone and testosterone concentrations were able to help determine sex of unknown individuals. Immunohistochemistry revealed that steroid hormones most likely do not leach out of whiskers based on the deposition patterns of progesterone and cortisol being present throughout the whisker length. Overall, measuring steroid hormones in whiskers can reveal individual reproductive histories over multiple years in sea lions and fur seals. Cyclical patterns of δ 15 N were useful for identifying periods of up to ~10 years of growth within whiskers, and measuring both stable isotopes and hormones may be useful for differentiating periods of active gestation from diapause and potentially track multi-year reproductive histories of female otariids.